2020
DOI: 10.1002/anie.201916675
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Impact of Gold(I)–Thiolate Motifs on the Aggregation‐Induced Emission of Gold Nanoclusters

Abstract: Aggregation‐induced emission (AIE) provides an efficient strategy to synthesize highly luminescent metal nanoclusters (NCs), however, rational control of emission energy and intensity of metal NCs is still challenging. This communication reveals the impact of surface AuI‐thiolate motifs on the AIE properties of Au NCs, by employing a series of water‐soluble glutathione (GSH)‐coordinated Au complexes and NCs as a model ([Au10SR10], [Au15SR13], [Au18SR14], and [Au25SR18]−, SR=thiolate ligand). Spectroscopic inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
191
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(195 citation statements)
references
References 49 publications
1
191
1
2
Order By: Relevance
“…further studied the influence of Au(I)‐thiolate motifs on the AIE of Au NCs. [48] They systematically studied the AIE behavior of a series of Au(I)‐SR complexes and Au NCs. They found that the emission mechanism of Au NCs is intrinsically affected by the length of Au(I)‐SR motifs.…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…further studied the influence of Au(I)‐thiolate motifs on the AIE of Au NCs. [48] They systematically studied the AIE behavior of a series of Au(I)‐SR complexes and Au NCs. They found that the emission mechanism of Au NCs is intrinsically affected by the length of Au(I)‐SR motifs.…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…However, in the early investigations, metal nanoclusters had very weak photoluminescence (PL), with quantum yield typically in the order of 0.1 % or less [17, 18] . Designing strategies are needed but the most fundamental issue; the origin of PL remains unclear [19–27] . There has been a considerable controversy surrounding the roles of the metal core (metal–metal interaction) and the shell (metal–ligand interaction).…”
Section: Figurementioning
confidence: 99%
“…[17,18] Designing strategies are needed but the most fundamental issue; the origin of PL remains unclear. [19][20][21][22][23][24][25][26][27] There has been a considerable controversy surrounding the roles of the metal core (metal-metal interaction) and the shell (metal-ligand interaction). In recent studies, several findings have been reported regarding the designing strategies for brighter cluster luminogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable achievements of X-ray crystallography in the past two decades suggest a universal core-shell structure scheme for [M n (SR) m ] q NCs, in which an M(0) core is capped by a monolayer of M(I)-SR protecting motifs. [9][10][11][12][13][14][15][16][17][18] Based on this molecule-like structure and the strong quantum connement effects in this ultra-small size regime, metal NCs exhibit many molecule-like properties, such as HOMO-LUMO transition, 10,12,13,19 strong luminescence, [20][21][22][23] intrinsic chirality, 24 and good catalytic activity. 5,[25][26][27] More intriguingly, almost all these molecule-like properties show an atomic-level dependency on the cluster structure.…”
Section: Introductionmentioning
confidence: 99%